1984
DOI: 10.1111/j.1399-0004.1984.tb00474.x
|View full text |Cite
|
Sign up to set email alerts
|

The psychological profile of the fragile X syndrome

Abstract: An attempt is made to present a more accurate description of the psychological profile of males with the fragile X syndrome after the evaluation of an unselected group of 21 affected patients. Except for one boy with slight mental retardation, all were moderately to severely mentally retarded, with retardation of motor development and pronounced speech disability. The most striking behavioral problem is hyperactivity together with concentration difficulties. A great number of patients show auto mutilation espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(31 citation statements)
references
References 2 publications
1
29
0
1
Order By: Relevance
“…For example, in their sample of 14 males with FXS (chronological (CA) range: 3 – 27 years), Bregman, Leckman, and Ort (1988) found that all participants demonstrated significant inattention and hyperactivity and 13/14 participants demonstrated clinically significant impulsivity problems. Fryns, Jacobs, Kleczkowska, and van den Berghe (1984) reported similar findings for a sample of 21 males between 2 and 21 years of age, describing “hyperkinetic behavior with restlessness, overactivity, agitation and poor, superficial attention (Fryns et al, 1984, pg. 133)” as the most salient behavioral characteristics of their sample.…”
Section: Introductionmentioning
confidence: 66%
“…For example, in their sample of 14 males with FXS (chronological (CA) range: 3 – 27 years), Bregman, Leckman, and Ort (1988) found that all participants demonstrated significant inattention and hyperactivity and 13/14 participants demonstrated clinically significant impulsivity problems. Fryns, Jacobs, Kleczkowska, and van den Berghe (1984) reported similar findings for a sample of 21 males between 2 and 21 years of age, describing “hyperkinetic behavior with restlessness, overactivity, agitation and poor, superficial attention (Fryns et al, 1984, pg. 133)” as the most salient behavioral characteristics of their sample.…”
Section: Introductionmentioning
confidence: 66%
“…Moderate to severe delays have been reported in all aspects of language development including expressive and receptive vocabulary, syntax, and pragmatics (Fryns, Jacobs, Kleczkowska, & Van den Berghe, 1984;Newell, Sanborn, & Hagerman, 1983;Roberts et al, 2001;Sudhalter, Scarborough, & Cohen, 1991). In addition to language delays, speech intelligibility in conversation is often poor (Paul, Cohen, Breg, Watson, & Herman, 1984;Spinelli, Rocha, Giacheti, & Richieri-Costa, 1995).…”
mentioning
confidence: 99%
“…The X chromosome-linked disorder is caused by loss of function of a single gene, fragile X mental retardation 1 (FMR1), most frequently by expansion of CGG repeats (>200 repeats) in the 5Ј regulatory region causing hypermethylation that results in transcriptional silencing (Heitz et al, 1992;Oberle et al, 1991;Pieretti et al, 1991). In addition to mental impairment, FXS patients also display a wide range of social interaction problems characterized by poor eye contact, hyperactivity, attention deficit and obsessive-compulsive behaviors (Boccia and Roberts, 2000;Cornish et al, 2001;Fryns et al, 1984;Torrioli et al, 2008), and hypersensitivity to sensory stimuli (Fryns, 1984;Hessl et al, 2001). Other physical anomalies include elongated face, prominent ears and enlarged male testes (Chudley and Hagerman, 1987;Giangreco et al, 1996;Moore et al, 1982).…”
Section: Introductionmentioning
confidence: 99%